2017
DOI: 10.1523/jneurosci.2552-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Architecture Shapes Initiation and Richness of Spontaneous Network Activity

Abstract: Spontaneous activity in the absence of external input, including propagating waves of activity, is a robust feature of neuronal networks and The neurophysiological and anatomical requirements for initiation and persistence of such activity, however, are poorly understood, as is their role in the function of neuronal networks. Computational network studies indicate that clustered connectivity may foster the generation, maintenance, and richness of spontaneous activity. Since this mesoscale architecture cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 68 publications
12
54
0
Order By: Relevance
“…We conjecture that metric effects overshadow the distribution of connections to such an extreme that they mold the dynamic attributes of the network. Such an idea is supported by experimental results in neuronal cultures [10,32]. For instance, the analysis of activity fronts in homogeneous cultures similar to ours (δ ≃ 0.1, Λ ≃ 0.2) revealed that metric correlations provide amplification mechanisms for the fronts to spontaneously emerge [10].…”
Section: Fig 2 Comparison Between Experiments and Nnim Exper-supporting
confidence: 86%
“…We conjecture that metric effects overshadow the distribution of connections to such an extreme that they mold the dynamic attributes of the network. Such an idea is supported by experimental results in neuronal cultures [10,32]. For instance, the analysis of activity fronts in homogeneous cultures similar to ours (δ ≃ 0.1, Λ ≃ 0.2) revealed that metric correlations provide amplification mechanisms for the fronts to spontaneously emerge [10].…”
Section: Fig 2 Comparison Between Experiments and Nnim Exper-supporting
confidence: 86%
“…heterogeneous in space, is able to reproduce remarkably well empirical in vitro results for neural cultures with different levels of mesoscopic structural heterogeneity (79).…”
Section: A4) Up-state Phasementioning
confidence: 83%
“…For example, Okujeni et al. reported that appropriately clustered networks underlie diverse synchronized firing patterns in vitro . There is also a possibility that “rich‐club” network structures support generation of synchronized firing patterns .…”
Section: Background and Objectivesmentioning
confidence: 99%